2020
DOI: 10.3389/fphar.2020.00883
|View full text |Cite
|
Sign up to set email alerts
|

Conventional Pig as Animal Model for Human Renal Drug Excretion Processes: Unravelling the Porcine Renal Function by Use of a Cocktail of Exogenous Markers

Abstract: Over recent years, pigs have been promoted as potential animal model due to their anatomical and physiological similarities with humans. However, information about the contribution of distinct renal elimination processes [glomerular filtration rate (GFR), effective renal plasma flow (ERPF), tubular secretion, and reabsorption] in pigs is currently limited. Therefore, a cocktail of renal markers, consisting of iohexol (GFR), para-aminohippuric acid (ERPF and net tubular anion secretion), pindolol (net tubular c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Throughout all the test scenarios, the computer script managed a simulated urine output fixed at 5 mL/min when the MAP was 50 mmHg or higher, mimicking a basal urine rate, and zero when the MAP dropped below this threshold. While the urine rate selected is above the upper limit of physiological urinary flow rates observed in swine of 2.03 +/− 1 mL/kg/h [ 26 ], the scenarios and testing setup can be adjusted to meet the needs of end users. The higher rate was selected due to peristaltic pump hardware limitations with slower flow rates.…”
Section: Methodsmentioning
confidence: 99%
“…Throughout all the test scenarios, the computer script managed a simulated urine output fixed at 5 mL/min when the MAP was 50 mmHg or higher, mimicking a basal urine rate, and zero when the MAP dropped below this threshold. While the urine rate selected is above the upper limit of physiological urinary flow rates observed in swine of 2.03 +/− 1 mL/kg/h [ 26 ], the scenarios and testing setup can be adjusted to meet the needs of end users. The higher rate was selected due to peristaltic pump hardware limitations with slower flow rates.…”
Section: Methodsmentioning
confidence: 99%
“…Since the mechanism of ARC is not yet clear, there are only limited animal studies on ARC have been reported. In these studies, iohexol and p -aminohippuric acid (PAH) were detected in blood as potential markers to evaluate the GFR, effective renal plasma flow and tubular secretion ( Dhondt et al, 2020 ; Stroobant et al, 2020 ). Dhondt et al used lipopolysaccharides (LPS) by continuous infusion to induce a sepsis piglets model, and elevated clearances of GFR marker iohexol and exogenously creatinine and effective renal plasma flow (ERPF) marker PAH were observed ( Dhondt et al, 2021b ).…”
Section: What We Will Domentioning
confidence: 99%
“…In the renal superficial veins, humans, cats, and dogs are reported to have ‘stellate veins’, whereas rats have only spur like veins [ 211 ]. The porcine renal function analytes such as creatinine, blood urea nitrogen (BUN) and anion secretion [ 22 , 23 , 212 ] are comparable to human’s. The size of pigs as well as other LAM allow for the serial collection of blood analysis for biomarkers.…”
Section: Interventions Of Aki Tested In the Porcine Modelsmentioning
confidence: 99%